Karyotypes of some species of the genus Lessingianthus (vernonieae, asteraceae) and taxonomic implications - Angulo, María Betiana (2014)
Fil: Angulo, María Betiana. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.